H90-10 single-chain antibody recognizes Hsp90beta by immunoprecipitation and Western blotting - Picard, Didier; Abboud, Ernest; Bernasconi, Lilia (Antibody Reports, 2021)
The recombinant antibody H90-10 detects the endogenous human heat-shock protein 90 beta (Hsp90β) by immunoprecipitation (IP) and Western blotting.